2012
DOI: 10.3109/1354750x.2012.664168
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers of apoptosis in the early period of heart transplantation

Abstract: The utility of specific apoptosis markers in peripheral blood for diagnosis of acute cellular rejection is low. Everolimus may have an anti-apoptotic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…The expression of IGFBP5 can reverse cisplatin resistance of ESCC [26]. On the other hand, CLAP-2, IGF-I and sTNF-R2 all anti-apoptotic proteins [27,28]. IGF-I can act on different apoptosis control points, including Bcl-2 family proteins, caspase inhibitors and death-induced receptor signal transduction [29].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IGFBP5 can reverse cisplatin resistance of ESCC [26]. On the other hand, CLAP-2, IGF-I and sTNF-R2 all anti-apoptotic proteins [27,28]. IGF-I can act on different apoptosis control points, including Bcl-2 family proteins, caspase inhibitors and death-induced receptor signal transduction [29].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, decoy receptor 2 (DcR2), a transmembrane receptor of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), is a cellular senescent marker with an ectodomain proven to be shearable and detectable (3,7,19). DcR2 is detected in both senescent tumor cells and fibroblasts (3,18).…”
mentioning
confidence: 99%
“…Many researches have reported that after cardiac transplantation myocardial cell showed an apoptosis process [31,32]. In current studies, myocyte apoptosis was detected in allografts, but not in isografts [33].…”
Section: Pkm2 Was Relevant To Cardiomyocytes Apoptosis In Allograftmentioning
confidence: 50%
“…Apoptosis, or "programmed cell death" is implicated in several different heart diseases, and the results observed in terms of the existence of a possible relationship between apoptosis and acute cellular rejection are disparate [33]. In addition, many enunciable studies intensively demonstrated the existence of apoptosis in cardiac tissue samples [32,33,37]. In general, most studies reveal a higher number of apoptosis parameters as the rejection grade increases.…”
Section: Discussionmentioning
confidence: 92%